Creation, effects on embryo quality, and clinical outcomes of a new embryo culture medium with 31 optimized components derived from human oviduct fluid: A prospective multicenter randomized trial. (11th April 2022) - Utsunomiya, Takafumi; Yao, Tatsuma; Itoh, Hiroko; Kai, Yufuko; Kumasako, Yoko; Setoguchi, Miwa; Nakagata, Naomi; Abe, Hiroyuki; Ishikawa, Motoharu; Kyono, Koichi; Shibahara, Hiroaki; Tsutsumi, Osamu; et al.
Abstract: Purpose: Our aim is to make an ideal embryo culture medium close to human oviduct fluid (HOF) components, and to evaluate the quality of this medium with embryo quality and clinical outcomes in assisted reproductive technology (ART) by a prospective randomized controlled trial (RCT). Methods: Study I: HOF was collected laparoscopically from patients ( n  = 28) with normal pelvic findings. According to HOF analysis results, the new medium "HiGROW OVIT ® " (OVIT) was designed. Study II: Embryos (2 pronuclei (2PN) = 9633) were assigned from 1435 patients. The blastulation rate (BR), good BR (gBR), utilized (transferred/cryo‐preserved) BR (uBR), pregnancy rate (PR), and miscarriage rate (MR) were compared between the OVIT and control groups by RCT. Results: The novel medium 'OVIT' was produced according to 31 HOF components. The concentrations of essential amino acids (e‐AAs) were lower in OVIT than in current media, yet the opposite was true for ne‐AA concentrations. gBR and uBR were higher in the OVIT group than in the control group. In the older female group, gBT and uBR were significantly higher in the OVIT group. Conclusions: The novel medium 'OVIT' was produced according to HOF data. The OVIT had significantly better embryo quality and clinical outcomes than the current media.